2015
DOI: 10.1007/978-3-319-05230-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Using Image-based CFD to Investigate the Intracardiac Turbulence

Abstract: A numerical framework designed to compute the blood flow in patientspecific human hearts is presented. The geometry of the heart cavities and associated wall motion are extracted from 4D medical images while the valves of the heart are accounted for thanks to low order geometrical models. The resulting blood flow equations are solved using a fourth-order low-dissipative finite-volume scheme and a mixed Aribtrary Lagrangian-Eulerian / Immersed Boundary framework. On top of retrieving the main fluid flow phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The intrinsic technical limitations of the CMR exams or the numerical strategies generally employed in LV CFD studies are likely to be responsible for the quasi-absence of studies about fluctuations, as they cannot grasp the entire nature of the flow. Fluctuations were reported in our previous studies 9,10 in an abnormal heart and very recently, using a new CMR method to evaluate the intensity and the localization of velocity fluctuations, Zajac et al 53 confirmed the presence of non-negligible in vivo level of "turbulent" kinetic energy in abnormal and normal LVs. As the nature of the flow directly affects the characteristic time scales and local levels of flow stresses, we believe that the analysis of the velocity fluctuations can provide a new paradigm in the assessment of the cardiovascular flow and mechanosensitive feedbacks.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…The intrinsic technical limitations of the CMR exams or the numerical strategies generally employed in LV CFD studies are likely to be responsible for the quasi-absence of studies about fluctuations, as they cannot grasp the entire nature of the flow. Fluctuations were reported in our previous studies 9,10 in an abnormal heart and very recently, using a new CMR method to evaluate the intensity and the localization of velocity fluctuations, Zajac et al 53 confirmed the presence of non-negligible in vivo level of "turbulent" kinetic energy in abnormal and normal LVs. As the nature of the flow directly affects the characteristic time scales and local levels of flow stresses, we believe that the analysis of the velocity fluctuations can provide a new paradigm in the assessment of the cardiovascular flow and mechanosensitive feedbacks.…”
Section: Introductionmentioning
confidence: 60%
“…The stroke volume is 68 mL and the ejection fraction is 62 %, which falls within the normal physiological range 31 . Details are provided in previous studies 9,10 . The aortic valve (AV) and the MV are difficult to extract from the medical images as they are thin and highly moving structures.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations